Influence of Blast Delay Time on Rock Fragmentation in a 22-FT Bench - Mark S. Stagg; Stephen A. Rholl (International Society of Explosives Engineers, 1988)
The Bureau of Mines is studying blast delay timing influences on rock fragmentation in a series of tests that started in 3-ft concrete blocks, progressed to 45in-bench reduced-scale tests in massive dolomite, and has now included 22-ft-bench full-scale tests in a thin-to-thick horizontally bedded dolomite. This paper discusses the full-scale test results and how they compared to the concrete block and reduced-scale studies.